Macroeconomic issues and policies in the Middle East and North Africa - Iqbal, Zubair (International Monetary Fund, 2001)
This book brings together recent research bt IMF staff on how the region's countries are grappling with these challenges. It rigorously analyzes policy alternatives for a range of relevant topics-including the implications of changing demographic trends for growth and unemployment, determinants of inflation, financial-sector reform and Islamic banking, fiscal sustainability in oil-dependent economies, exchange rate and trade arrangements, and impediments to foreign direct investment. The book's overall theme is that self-sustaining and faster growth can be achieved through compehensive structural reforms and closer collaboration between the region's policymakers and the international community.